Produksi Kit Immunoradiometricassay (IRMA) CA-125 untuk Deteksi Dini Kanker Ovarium - PUJI WIDAYATI; AGUS ARIYANTO; WENING LESTARI (Fakultas Farmasi Universitas Pancasila, 2009)
Ovarian cancer is the second highest incidence after cervix cancer, but has higher fatality level than cervix cancer. Generally, patient is known suffering ovarian cancer in very late stadium, III or IV, which is almost incurable. Cancer Would be easier to cure if detected early. In blood of ovarian cancer patient, Carbohydrate Antigen-125 (CA-125), an antigenic glycoprotein, is presence in a very low concentration initially and will increase proportionally with the level of malignancy. Therefore, early detection of ovarian cancer can be carried out by measurement of low level CA-125 in the blood. The most suitable method for the measurement is immunoradiometricassay (IRMA). Our laboratoryhas developed CA-125 IRMA kit since 2003, at first in form of CA-125 IRMA kit components that consisted of 125I-CA-125 tracer, CA-125 standard, and monoclonal antibody-coated tubes. We then made assay optimization of the IRMA CA-125 kit which gave B/T value of 19.05%, NSB value of 0.53% and Working area of 0 to 200 mIU/mL. Our further Works on validation of IRMA CA-125 kit using high and low concentration quality control (QCH and QCL) showed an intra assay (n=15) CV value of 9.9% for QCL and 2.97% for QCH, While inter assay (n=7) CV value of 13.1% and 4.9% for QCL and QCH respectively. The results comply with the IAEA protocol requirement.